(untitled) (Research, Society and Development, 2020)
This final project is made to analyze the current business of PT Angkasa Pura II (Persero), by analyzing the internal and external factors of the Hotel business environment in the Airport City area of Kualanamu International Airport today. Then, it is expected to analyze the Hotel Business Model Strategy that is appropriate for hotel businesses in the Airport City Area of Kualanamu International Airport to be developed and the final step is to analyze the results of the implementation hotel strategies in the Airport City Area of Kualanamu International Airport in the face of competition in the current era of global competition. To achieve the objectives of this study, the proposed business strategy used by the author is SWOT Analysis, then proceed with the decision-making stage. The technique in question is the quantitative Strategy Planning Matrix (QSPM) technique. QSPM analysis tool is an analysis tool used to evaluate alternative strategic choices objectively according to internal and external factors that have been identified previously. Finally, the conclusion is based on the results of the analysis that has been done.